Household portfolio allocations: Evidence on risk preferences from the household, income, and labour dynamics in Australia (HILDA) survey using Tobit models - Safdar Ullah Khan; Satyanarayana Ramella; Habib Ur Rahman; Zulfiqar Hyder (Journal of Risk and Financial Management, 2022)
This study investigates intrahousehold risk preferences in household portfolio decision-making. Most household finance data are collected at the household level, and it is challenging to come up with an explanation of risk-taking decisions and have a direction on the within-household bargaining mechanisms. We provide these challenging pieces of evidence by applying a Tobit model on panel data taken from waves 2 to 6 of HILDA surveys. Overall, the results indicate that the risk-taking attitude of partners matters in household portfolio allocations. Risk-averse males and their female counterparts invest less in risky assets. Compared with the no-conflict (identical risk preferences) group, male partners with risk-loving behaviour tend to invest more in risky assets. Further, individual risk preferences are sensitive to fluctuations in equity and housing markets in Australia. Taken together, one of the crucial implications of our findings for future research is that household-bargaining models should, perhaps, give more bargaining power to risk-loving males, offering an additional explanation for the determinants of risk-taking behaviour of households. Understanding the risk-taking attitudes of households is important for future work to understand the fraction of households that end up with a negative net worth in recessions or crisis conditions, such as financial crises, pandemics, and wars.
Keywords: 330; intra-household portfolio choice; risk preferences; HILDA surveys; Tobit models